Der hörbare und der unhörbare Unterschied - Böger, C. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
Sports movement is based on a rhythm which serves as a time frame. Gröben (2000) points out that movement parameters, like the time structures which develop from the rhythm of movement, can be influenced by instructions. There is every reason to believe that it is possible to influence the interaction between perception and action. The aim of this study is to use synchronisation experiments to analyse the interaction between auditory perception and action. A further goal is to check the effect of metaphorical instructions on the timing of an action in motor learning.